ANALYZING RESTAURANT ATTRIBUTES OF K8 COFFEE HOUSE AND RESTO IN MANADO USING IMPORTANCE PERFORMANCE ANALYSIS - Warokka, Gloria F.; Pangemanan, Sifrid S.; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Restaurant business is growing in line with the customer’s needs, wants and demands. The restaurant business has become a business that have concept of   ambience, selling, menu and packaging, and also service. This research aims to analyze the restaurant attributes of K8 Coffee House and Resto Manado. Restaurant Attributes has four indicators namely ambience, menu, food quality and service quality. This is a quantitative descriptive research and used IPA as the measurement tool. The sample size of this research is 100 respondents who already visited the K8 Coffee House and Resto. Convenience sampling was used by collecting data through online questionnaire. The result revealed that food quality is located in Quadrant II that indicated a high level of importance and good performance. In Quadrant I, there is ambience which have high importance but the level of performance is lower. Meanwhile, service quality is located in Quadrant III which means this attribute is not too important to the customers and the company deliver low performance. And the last is Menu that located in Quadrant IV. This attribute has low importance to the customers but high performance which means this attribute could be the strength of K8 Coffee House and Resto Manado. Keywords: restaurant attributes, importance and performance analysis.